"Did you do your homework?" Mathematics teachers' homework follow‐up practices at middle school level. Issue 1 (28th October 2018) - Rosário, Pedro; Cunha, Jennifer; Nunes, Ana Rita; Moreira, Tânia; Núñez, José Carlos; Xu, Jianzhong
Abstract: Teachers' homework follow‐up practices, the in‐class strategies teachers use to monitor their students' homework assignments, have an impact on their students' homework behaviors and academic achievement. The current study explored the perspectives of middle school mathematics teachers on the three domains of homework follow‐up: the practices used in class, the purposes of each practice, and the aspects that may influence this process. Data were collected from two data sources (i.e., focus groups and classroom observations) and were analyzed using thematic analysis. The findings showed that teachers monitored homework either using a single strategy or a combination of strategies (e.g., checking homework completion and providing individual feedback) linked to a specific purpose (e.g., promote students' involvement). The teachers also reported that they were under certain constraints when they delivered homework follow‐up practices (e.g., pressure to follow the curriculum), so their practices' effectiveness sometimes can be compromised. Implications for practice are discussed.